Exercise Habits, Hematogram and Blood Chemistry of Diabetes Mellitus Patients at Risk For Metabolic Syndrome, Bantul Public Health Center - Hidayati, Titiek; M Gugun, Adang; Akrom (International Journal of Psychosocial Rehabilitation, 2020)
Exercise habits are one of the WHO recommendations as a form of non-pharmacological therapy in patients with DM. This study was conducted with a cross-sectional design in 99 patients at risk for DM. The mean of GDS, cholesterol, and triglyceride levels were subjected to a mean difference test with a one-way t-test with 95% significance. The results show that the majority of the research subjects are women, basic education, private employment, exercise habits, average blood cavern level and fasting higher than the target (257.88 ± 117.76 mg/dl), and triglyceride levels (204.66 ± 103.83 mg/dl). There are also Hb levels (12.95 ± 1.49), leukocyte count (8.96 ± 1.96), platelet counts (321.24 ± 0.74) and erythrocytes (4.53 ± 0.55). The cholesterol level of the test subject is also within the normal range (169.72 ± 39.23 mg/dl). The results show that the Hb and hematocrit levels of the exercise group are higher than the non-exercise group (p <0.05). Based on the results of the study, it can be concluded that exercise activities are associated with an increase in Hb and in hematocrit levels in DM patients at the public health center of Jetis, Bantul. Jetis Bantul Health Center.